A study of the influence of workplace environment on job performance of staff at Pejabat Setiausaha Kerajaan Negeri Pahang / Nur Azidah Mokhtar - Mokhtar, Nur Azidah (Faculty of Business and Management, 2017)
The purpose of this study is to analyze the relationship between the workplace environments with job performance in Pejabat Setiausaha Kerajaan Negeri Pahang. This study is conducted to measure employees workplace environments satisfaction and job performance and to analyse the etTect of workplace environments satisfaction towards job performance. The questionnaires had been distributed randomly to the employees in Pejabat Setiausaha Kerajaan Negeri Pahang. The respondents for this study were 50 respondents. After collected the questionnaires from the respondents, the data had been analyzed by using Statistical Packages for the Social Sciences (SPSS) version 20 to get the results. Based on the findings, adaptive performance inf1uences the employee of Pejabat Setiausaha Kerajaan Negeri Pahang the most. The findings also show that the level of employee's workplace environment satisfaction at Pejabat Setiausaha Kerajaan Negeri Pahang is high.